Experimental Verification of the Reading Comprehension Intervention for the German Language as L3 - Szabó, Erzsébet; Stranovská, Eva; Ficzere, Anikó (Journal of Education Culture and Society, 2022)
Aim. The main aim of the research was to verify the reading comprehension intervention program for the German language that builds on complex models of foreign language text comprehension while stimulating the cognitive, affective and social levels of reading. Methods. The respondents of the research were studying English language in their 3rd year in secondary schools in Slovakia. The data were collected with the didactic reading comprehension test for the German language (Hockicková et al., 2020). The research was conducted through a pre-test before the intervention program and a post-test after the intervention. The basic characteristics of the examined variables were described using descriptive statistics. A paired t-test was used to detect differences in reading comprehension before and after the intervention. Results. The results of the research confirmed an increase in German texts comprehension in each experimental group. A statistically significant difference in reading comprehension performance was not confirmed in the control groups without completing the intervention program. Conclusion. The reading comprehension intervention program for the German language at A2 level appears to be effective in the direction of increasing performance in reading comprehension of German texts. The intervention in German text comprehension is manifested in two simultaneous work practices, namely in the development of predictors and in working with different types of texts as well as different reading strategies.